Pengaruh kualitas pelayanan , sanksi pajak, dan razia lapangan terhadap kepatuhan Wajib Pajak di Kabupten Malang Selatan - Putri, Demes Greta Amalia; Listyowati, Listyowati; Werdiningsih, Sri (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2024)
This study aims to determine the effect of Service Quality, Tax Sanctions and Field Raids on Taxpayer Compliance in paying taxes for two-wheeled motorized vehicles in South Malang Regency. In this study using primary data, with a total sample of 100 respondents, which were taken using the Simple Random Sampling method, namely random sampling so that each member of the population has the same opportunity to be a member of the sample. Data collection techniques used questionnaires distributed through journals and google forms. The data analysis used is multiple linear regression, regression model test (F test), determinant coefficient test (R2) and hypothesis test (t test) using the SPSS 26 application. Based on the results of the analysis, it shows that the Tax Sanctions Variable has an effect on taxpayer compliance. While the variable Service Quality and Field Raids variables have no effect on taxpayer compliance in paying taxes for two-wheeled vehicles in South Malang Regency.